2019
DOI: 10.1099/mgen.0.000314
|View full text |Cite
|
Sign up to set email alerts
|

O-antigen biosynthesis gene clusters of Escherichia albertii: their diversity and similarity to Escherichia coli gene clusters and the development of an O-genotyping method

Abstract: Escherichia albertii is a recently recognized human enteropathogen that is closely related to Escherichia coli . In many Gram-negative bacteria, including E. coli , O-antigen variation has long been used for the serotyping of strains. In E. albertii , while eight O-serotypes unique to this species have been identified, some strains have been shown to exhibit genetic or serological similarity to known E. coli / Shigella O-serotypes. However, the diversity of O-serotypes and O-antigen biosynthesis gene clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 45 publications
(34 reference statements)
4
39
0
Order By: Relevance
“…Bacterial strains used and sequenced in this study are listed in Supplementary Table 1. Twenty-nine E. albertii strains were described previously 3,22 . Bacterial culture media preparation.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strains used and sequenced in this study are listed in Supplementary Table 1. Twenty-nine E. albertii strains were described previously 3,22 . Bacterial culture media preparation.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that 38 of the E. albertii strains were shared by 19 other Ogenotypes and six strains were untypable (Table 1); however, the result from EC15062 was previously described (5). Among these, 24 strains were agglutinated with certain antisera of E. coli O-antigens ( Table 1).…”
Section: Accepted Manuscriptmentioning
confidence: 80%
“…All E. albertii strains were subjected to PCR for EAO-genotyping (5). In EAOgenotyping, 40 primer pairs to specifically detect each O-genotype and two primer pairs for an internal control were used.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, if TccP3 could act similarly to modulate the inflammatory response of the host cell, it is a question that remains to be explored in further studies. Regarding TccP3, it may be noteworthy that our preliminary analysis of the prevalence of tccP3 in 243 E. albertii genomes (Ooka et al, 2019) identified only five tccP3-positive strains (including strain 1551-2). However, as there is considerable difficulty in searching for tccP family members in draft genome sequences due to the presence of internal repeats, more detailed analyses are required to determine the precise prevalence of tccp3 genes and their intactness.…”
mentioning
confidence: 91%